The Intersectionality Toolbox: A Resource for Teaching and Applying an Intersectional Lens in Public Health - Sabik, Natalie J. (Frontiers in Public Health, 2021)
Intersectionality is a theoretical framework that was developed to address the ways in which people's experiences are shaped based on their intersecting social identities (e. g., race/ethnicity, gender, class, age, etc.). This approach focuses on the importance of considering power, privilege, and social structures in relation to people's access to resources, experiences of discrimination, and interpersonal interactions. An intersectional approach in public health is critical for research and teaching to illuminate health disparities and the underlying structures that create and maintain disparities. While scholars have focused primarily on how to integrate an intersectional perspective into research methods, there is a need for a clear framework for applying intersectionality effectively in public health teaching. The Intersectionality Toolbox (ITB) is a framework developed from a variety of interdisciplinary resources designed to apply an intersectional perspective to public health issues. This article describes the Intersectionality Toolbox and details how it can be utilized in public health classes. Following a course where the ITB was implemented, student feedback was sought to determine the appropriateness and effectiveness of the design, and metrics were aligned with the learning outcomes. The ITB was refined and retained to integrate into courses and assignments focused on teaching about the intersecting nature of the social determinants of health.